KOMUNIKASI DAKWAH DI ERA CYBER - Julis Suriani (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2018)
In this era of globalization at the present time, there are many ways we can do to carry out da'wah. Unlike when humans have not known whose name technology. Now mushroomed social media accounts that can be owned by someone. Not only that beautiful writings and verses can be heard all over the world. As we know that every believing Muslim is obliged to carry out da'wah despite one verse. The people who mepunyai science is supposed to menyebrkan knowledge he has. So that science is not only in him. Da'wah is a worship for every Muslim who believes, giving da'wah is part of alms, if the message of dakwah is not ignored by mad'u its not an important issue already convey. Even if the message of dakwah that we conveyed to his heart means alhamdulillah and if it can change his behavior from the bad then change to the good means we both get blessing.